Bioactivity and viscoelastic characterization of chitosan/ bioglass® composite membranes - Caridade, S. G. (2012)
Membranes of chitosan (CTS) and composite membranes of CTS with bioglass are prepared by solvent casting. The composite membranes are shown to induce the precipitation of apatite upon immersion in SBF. The biomineralization process is followed by measuring the variation of the viscoelastic properties of the membranes immersed in SBF, both online and offline. Nonconventional DMA is used to measure the change in the storage modulus, E0, and the loss factor, tan d, as a function of the immersion in SBF. A simple model is used to estimate the E0 of the apatite layer formed in vitro that is about 130 MPa. This work shows that innovate mechanical tests can be useful to characterize the mechanical performance of composites under physiological conditions.